The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs. (1st February 2023) - Pi, Yixing; Liang, Zitian; Jiang, Qianzhou; Chen, Ding; Su, Zhikang; Ouyang, Yuanting; Zhang, Zhiyi; Liu, Jiaohong; Wen, Siyi; Yang, Li; Luo, Tao; Guo, Lvhua
Abstract: Angiogenesis is a biological process in which resting endothelial cells start proliferating, migrating and forming new blood vessels. Angiogenesis is particularly important in the repair of bone tissue defects. Naringin (NG) is the main active monomeric component of traditional Chinese medicine, which has various biological activities, such as anti-osteoporosis, anti-inflammatory, blood activation and microcirculation improvement. At present, the mechanism of naringin in the process of angiogenesis is not clear. PIWI protein-interacting RNA (piRNA) is a small noncoding RNA (sncRNA) that has the functions of regulating protein synthesis, regulating the structure of chromatin and the genome, stabilizing mRNA and others. Several studies have demonstrated that piRNAs can mediate the angiogenesis process. Whether naringin can interfere with the process of angiogenesis by regulating piRNAs and related target genes deserves further exploration. Thus, the purpose of this study was to validate the potential angiogenic and bone regeneration properties and related mechanisms of naringin both in vivo and in vitro. Highlights: Angiogenesis effects of the naringin were investigated in vivo and in vitro. PIWI-interacting RNA (piRNA) is involved in naringin pro-angiogenic process. Angiogenesis-associated "piRNA-mRNA" interaction network was constructed.